Human sexuality in a world of diversity - RATHUS, Spencer A.; Jeffrey S. Nevid; Lois Fichner-Rathus (Boston : Allyn and Bacon, 1997)
Canada in the twenty-first century is rapidly evolving with respect to sexuality and relationships. Human Sexuality in a World of Diversity embraces and affirms sexual diversity. Indeed, it is this approach, adopted throughout every chapter, that makes this textbook unique. Before writing this edition, we searched extensively for new Canadian materials from a number of sources, including Canadian researchers
Includes bibliographical references and index
Keywords: Sex -- Textbooks. Sex customs -- Canada -- Textbooks